Family involvement and school effectiveness in primary education - Aierbe-Barandiaran, Ana; Bartau-Rojas, Isabel; Oregui-González, Eider (Anales de Psicología / Annals of Psychology, 2023)
The commonly accepted premise that collaboration among the educational community leads to school improvement and greater student achievement is not always fulfilled due to the diverse reality of schools and various initiatives to promote family participation. This work addresses the perception of teachers, school management teams and educational inspection of family-school-community relations in 23 primary schools in the Basque Autonomous Community, characterized by different criteria related to school effectiveness-ineffectiveness, aiming to identify good practice leading to school improvement. The study is descriptive-exploratory-exploratory-explanatory with mixed methodology, using questionnaires, in-depth interviews and discussion groups. Results show family involvement is mediated by teaching staff´s personal factors, that all schools try to promote family collaboration, though forms of participation vary, and those which work best are proactive, stressing different collaboration dimensions. Conclusions include adopting a systemic approach, review and updating of training modalities, and assessment of teaching competences for collaboration.